Investigation of keratolytic impact of synthetic bolalipids on skin penetration of a model hydrophilic permeant - Abdelrahman, Namarig; Drescher, Simon; Ann Dailey, Lea; Klang, Victoria (European journal of pharmaceutics and biopharmaceutics, 2024)
[Display omitted] •Single-chain bolalipids PC-C24-PC and PC-C32-PC do not enhance skin penetration of a hydrophilic permeant from aqueous vehicles into porcine ear skin.•Single-chain bolalipids strongly reduce corneocyte cohesion during ex vivo tape stripping.•The effect on corneocyte cohesion resembles the behavior observed for salicylic acid as keratolyic reference substance. Synthetic single-chain bolalipids (SSCBs) are novel excipients in drug delivery, with potential as stabilizers or solubilizers. However, their impact on skin barrier function has not been comprehensively studied. Therefore, two SSCBs (PC-C24-PC and PC-C32-PC) were studied in aqueous systems for their impact on penetration of a model permeant into porcine skin. Concentrations of 0.05 – 5 % w/w were tested; PC-C24-PC formulations were low-viscosity liquids while PC-C32-PC formed viscous dispersions to gels at room temperature. Formulations were compared for their ability to enhance sodium fluorescein penetration (SF, 0.1 % w/w) into skin via tape stripping. Using NIR-densitometry, the effect of SSCB formulations on corneocyte cohesion was evaluated. Data were compared with phospholipid mixture Lipoid S-75, sodium dodecyl sulfate (SDS), and polyethylene glycol 12-hydroxystearate (PEG-HS), and distilled water as negative control. Contrary to the hypothesis, both SSCBs failed to increase SF penetration into the stratum corneum, but rather showed a significant decrease in penetration depth compared to water. Both SSCBs exhibited a keratolytic effect at 5 % w/w, leading to substantial removal of proteins from the skin surface. Consequently, SSCBs may not enhance penetration of hydrophilic drugs into skin, but could be used as keratolytic agents.